Centers of value and the quest for meaning in faith development: A measurement approach - Mallery, Suzanne T.; Mallery, Paul (Frontiers in Psychology, 2022)
James Fowler’s 1981 model of faith development conceptualized “faith” as the quest for and maintenance of meaning oriented around centers of value which may or may not be religious or spiritual in nature. Although this model foreshadowed later work in meaning in life, substantial bodies of literature have developed in each area, almost entirely independently of the other. Integration has been hindered by measurement difficulties in faith development work. Fowler’s stages of faith development and their reformulation as Streib’s religious styles are usually measured through either a lengthy Faith Development Interview or short measures that do not assess the breadth of domains covered in the interview. These short measures are in many cases oriented around religious faith and impossible for a nonbeliever to answer. Embedded within the original model and the interview are aspects of faith development including perspective taking, social horizon, morality, locus of authority, form of world coherence, and symbolic function. A new Centers of Value and Quest for Meaning Scale is proposed to assess the aspects, allow nonbelievers to respond, tap centers of value that are not religious, and eventually address the theoretical assumption of structural wholeness across aspects. In a series of exploratory factor analyses, factors for each adult stage/style emerged for most of the aspects. This supports the potential importance of assessing the aspects and allows for more than one methodology to assess them.